2017
DOI: 10.1016/s1470-2045(17)30240-1
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab for patients with previously treated metastatic or recurrent non-small-cell lung cancer (JAVELIN Solid Tumor): dose-expansion cohort of a multicentre, open-label, phase 1b trial

Abstract: Background Avelumab, a fully human IgG1 immune checkpoint inhibitor targeting programmed death ligand 1 (PD-L1), has shown antitumour activity and an acceptable safety profile in patients with advanced solid tumours. Here, we assessed avelumab treatment in patients with advanced, platinum-treated non-small cell lung cancer (NSCLC). Methods In this dose-expansion cohort of a multicentre, open-label, phase 1 study, patients with progressive or platinum-resistant metastatic or recurrent NSCLC were enrolled at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
262
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 265 publications
(272 citation statements)
references
References 35 publications
7
262
0
3
Order By: Relevance
“…Most of the infusion reactions occurred after the first two infusions and were mild to moderate in severity. They did not lead to treatment discontinuation with modern supportive care (9). This observation is perhaps due to the unique construct of avelumab which will be further characterized in large ongoing phase 3 trials.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Most of the infusion reactions occurred after the first two infusions and were mild to moderate in severity. They did not lead to treatment discontinuation with modern supportive care (9). This observation is perhaps due to the unique construct of avelumab which will be further characterized in large ongoing phase 3 trials.…”
mentioning
confidence: 83%
“…It was recently approved for patients with chemotherapy-refractory metastatic Merkel cell carcinoma (8). In a recent issue of Lancet Oncology, Gulley and colleagues reported a multicenter, open-label, phase 1b trial of avelumab for patients with previously treated metastatic or recurrent NSCLC (9). This was a dose-expansion cohort of a dose-escalation phase 1a trial (JAVELIN solid tumor) after avelumab demonstrated antitumor activity with an acceptable adverse event profile in patients with advanced solid tumors (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Monoclonal antibody drugs that target the interaction between PD-1 and PD-L1 have shown dramatic and/or durable responses in a subset of NSCLC patients (3)(4)(5)(6), leading to FDA approvals of three agents (nivolumab, pembrolizumab, and atezolizumab) for treatment of metastatic NSCLC patients. Other agents that also target this pathway, such as durvalumab (7) and avelumab (8), are currently under clinical development.…”
mentioning
confidence: 99%